Réponses

2013-06-28T17:03:59+02:00

Bonjour,

 

Je vais considérer que ton expression est :

3^2\times \left(3^{-3}\right)^2

Ensuite, on utilise les formules du cours pour simplifier :

\left(a^b\right)^c = a^{bc}\\ a^b\times a^c = a^{b+c}

Ce qui donne :

3^2\times \left(3^{-3}\right)^2\\ =3^2\times 3^{-3\times 2}\\ =3^2\times 3^{-6}\\ =3^{2-6} = 3^{-4}

2013-06-28T17:05:47+02:00

3² × 3⁻³ × 2  =  3²⁻³ × 2

                  =  3⁻¹ × 2

                  =  1/3 × 2

                  =  2/3

 

 

 

3² × (3⁻³)²  =  3² × 3⁻⁶

                =  3⁻⁴

                =  1/3⁴

                =  1/81